Vagueness of Article 271 of the Indonesian National Criminal Code on Necrophilia as an Uncivilized Act Against Corpses - Andika Dian Tetuko; Nurini Aprilianda; Lucky Endrawati (State Islamic University of North Sumatra Indonesia, 2026)
This article examines the vagueness of Article 271 of Law Number 1 of 2023 concerning the Indonesian National Criminal Code in relation to necrophilia as an uncivilized act against corpses. The main problem lies in the open-ended phrase “treating a corpse in an uncivilized manner,” which does not explicitly clarify whether sexual acts against a corpse fall within its scope. This study uses normative legal research with statutory, conceptual, case, and comparative approaches. The analysis focuses on the National Criminal Code, the principle of legality, the lex certa requirement, the Mojokerto case, and comparative models from England and Wales, the United States, and India. The study finds that Article 271 provides an initial normative basis for protecting corpses, but its vague formulation may create uncertainty in prosecution, evidentiary construction, and judicial interpretation. This article argues that necrophilia should be regulated more explicitly as a sexual act against a corpse, either through an additional provision under Article 271 or through a separate offence. Such regulation is necessary to protect human dignity after death while maintaining legal certainty and limiting excessive interpretation in criminal law enforcement.